Vegetation structure and diversity of liberoid coffee agroforestry (Coffea liberica and Coffea dewevrei) across contrasting ecosystems in Indonesia - DANNIARY ISMAIL FARONNY; MELATI JULIA RAHMA; BENEDIKTUS BRAHMANTYO ADHI NUGROHO; SOEMARNO SOEMARNO; WENNY BEKTI SUNARHARUM; LUCHMAN HAKIM; JATI BATORO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Faronny DI, Rahma MJ, Nugroho BBA, Soemarno, Sunarharum WB, Hakim L, Batoro J. 2026. Vegetation structure and diversity of liberoid coffee agroforestry (Coffea liberica and Coffea dewevrei) across contrasting ecosystems in Indonesia. Biodiversitas 27 (5): d270536. https://doi.org/10.13057/biodiv/d270536. Climate change is projected to substantially reduce the climatically suitable range of Coffea arabica and Coffea canephora by 2050, elevating the strategic importance of the liberoid coffee group, comprising Coffea liberica and Coffea dewevrei, as climate-adaptive alternatives. This study characterized vegetation structure and associated species diversity of liberoid coffee agroforestry across three contrasting ecosystems in Indonesia: volcanic mountain agroforestry (Wonosalam, East Java), coastal agroforestry (South Malang, East Java), and tropical peatland agroforestry (Tanjung Jabung Barat, Jambi). Using nested quadrat sampling (18 plots; 400 m² each), vegetation data were analyzed through Importance Value Index (IVI) and Shannon-Wiener diversity indices (H'), vertical and horizontal canopy profiling, and NMDS ordination with Bray-Curtis dissimilarity. A total of 893 individuals representing 40 species from 23 families were recorded. C. dewevrei dominated mineral-soil systems in Wonosalam and South Malang, while C. liberica was the exclusive Coffea taxon in the Jambi peatland. Shannon diversity ranged from H': 0.72 to 2.13, with the highest mean diversity recorded at South Malang (H': 1.63); this gradient does not follow the pattern expected from ecosystem productivity alone, but rather a pattern in which farmer management decisions are a contributing factor, though management variables were not directly measured. NMDS ordination (stress: 0.029) revealed near-complete floristic separation of peatland communities from mineral-soil sites (Bray-Curtis: 0.93-0.94), reflecting ecosystem-level divergence under extreme organosol conditions. Musa paradisiaca and Leucaena leucocephala were identified as cross-ecosystem companion species in mineral-soil systems. These studies provide an observational framework for ecosystem-differentiated supporting climate-adaptive liberoid coffee cultivation, contingent on expanded replication and direct environmental monitoring.